Determinant Factors Enhancing the Financial Accountability of Village-Owned Enterprises - Handayani, Asih; Anisa, Anisa; Purwasih, Desy; Rosharlianti, Zulfa (International Journal of Economics and Financial Issues, 2025)
The uniqueness of BUMDes in terms of business form and purpose is what makes financial accountability important to be presented in the management of BUMDes to ensure that village funds are used effectively and efficiently, and maintain public trust in the management of BUMDes itself. Therefore, this study was conducted to examine the factors that affect financial accountability both directly and indirectly. The research data collected were from 434 respondents from the BUMDes Management in Banten Province. Furthermore, the data was analyzed using SmartPLS 4 Software using SEM-PLS after validity and reliability testing. The results of the study show that the information technology utilization, implementation and administration, as well as internal control systems, have a significant effect on financial accountability through the mediation of the financial reporting quality. Although the information technology utilization, implementation and administration, and internal control systems directly affect the financial reporting quality, the three have not been proven to have a direct effect on financial accountability. In addition, human resource competence has not been proven to have an effect either directly or indirectly on financial accountability or the quality of financial reporting.